Übersetzung als komplexer kognitiv basierter Prozess - Legutko-Marszałek, Iwona (Wydawnictwo Naukowe UAM, 2011)
The following article concentrates on cognitive aspects of the translation. We are interestedin course of the translation process in the brain, which is one of the most complicated processes connected with language. It integrates not only the linguistic perception and production,but also code-switching. During the translation process occurs activation of the linguistic information organized in mental lexicon, along with the nonlinguistic knowledge stored in other components of the memory.
Cognitive aspects of the translation
Keywords: Translation process; Lexical access; Mental lexicon; Cognitive processes